2018
DOI: 10.1163/22238980-00001061
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity and heritability in Eragrostis tef under irrigated Mediterranean conditions

Abstract: Tef (Eragrostis tef (Zucc.) Trotter) is a C4 annual cereal, common in Ethiopia, where it was presumably domesticated. Worldwide interest in tef cultivation and consumption has considerably increased in the last few decades because it is a gluten-free grain with high nutritional value. Here we report on the genetic diversity and heritability in a tef germplasm collection characterized in Israel. A total of 408 accessions of tef held in the Israel Gene Bank were grown in 2015 under common garden (screen-house) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Three tef accessions, RTC-144, RTC-405, and RTC-406, were selected from the available germplasm ( Ben-Zeev et al, 2018 ). Among 273 tef accessions examined in this field study, both RTC-405 and RTC-406 were found suitable for Mediterranean climate and used as standards in our earlier trials.…”
Section: Methodsmentioning
confidence: 99%
“…Three tef accessions, RTC-144, RTC-405, and RTC-406, were selected from the available germplasm ( Ben-Zeev et al, 2018 ). Among 273 tef accessions examined in this field study, both RTC-405 and RTC-406 were found suitable for Mediterranean climate and used as standards in our earlier trials.…”
Section: Methodsmentioning
confidence: 99%
“…Four accessions of tef (RTC-2, RTC-119, RTC-361, and RTC-400) were selected from the collection described in our previous work [12] due to their similar phenology. RTC-2 has white seeds, a high biomass, and a loose panicle.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Tef is grown in Israel during the dry summer, when irrigation must be applied to support crop production [12]. This need was exacerbated by the high temperatures of the Hula Valley.…”
Section: Lodgingmentioning
confidence: 99%
“…Recently, tef has been gaining popularity in many Western countries due to its dual potential-as a gluten-free "super food" grain [3], and as high-quality forage [4,5]. In Israel, the demand for tef grain is further increased by the Ethiopian descent citizens who continue to consume it for their traditional cuisine [6].…”
Section: Introductionmentioning
confidence: 99%